Metabolic Activity by (18)F-FDG-PET/CT is Prognostic for Stage I and II Pancreatic Cancer - Pimiento, Jose M. (Clin Nucl Med, 2016)
PURPOSE: Metabolic activity, as defined by 18F-fluorodeoxyglucose (FDG) uptake on positron emission tomography (PET), is a prognostic marker for multiple malignancies; however, no study has examined the prognostic value of imaging with FDG PET in stage I and II pancreatic cancer. We examined the value of PET FDG uptake in early-stage pancreatic cancer patients. METHODS: We identified patients with early-stage pancreatic cancer (I–II) who had FDG PET scan performed as part of their preoperative evaluation. Patients were divided by the median primary tumor standard uptake value (SUVmax) into either high or low FDG uptake. Our primary endpoints were overall survival (OS) and recurrence-free survival (RFS). Kaplan-Meier estimate was used for survival analysis. Pathologic data were compared using Fisher's exact and chi-square tests. RESULTS: 105 patients were identified: 51 patients with low-FDG uptake and 54 patients with high-FDG uptake. Eighty-five (81%) patients had PET avid tumors, whereas 20 (19%) patients did not. High-FDG uptake correlated with pathologic stage (P=0.012). Patients with low-FDG uptake had significantly better median OS than patients with high-FDG uptake (28 vs. 16 months; P=0.036). Patients with low-FDG uptake had significantly longer median RFS than patients with high FDG uptake (14 vs. 12 months; P=0.049). CONCLUSIONS: Low FDG uptake in PET scans in patients with stage I and II pancreatic cancer correlates with improved OS and RFS. This supports the concept that glucose metabolic pathways are important in pancreatic cancer biology and that PET scan activity can be used as a prognostic biomarker after pancreatectomy.